Analisis Faktor Psikologis dan Sosial yang Menghambat Partisipasi Aktif Mahasiswa - Jasmine Nur Annisa; Amanda Vergil Setyaningsih; Annisa Puji Rahayu; Sephira Rahmadani; Joko Tri Nugraha (PANDITA: Interdisciplinary Journal of Public Affairs, 2026)
Active student participation is an important indicator of learning quality because it reflects students’ willingness to engage in academic interaction, collaboration, and classroom activities. However, students’ participation is not only shaped by the learning environment but also by psychological and social conditions that influence their confidence and involvement. This study aims to analyze the effect of psychological factors on social factors that support students’ active participation in the academic environment. The study employed a quantitative approach with a causal associative design. The research sample consisted of 102 students selected using a simple random sampling technique. Data were collected through a structured questionnaire measuring psychological and social factors related to active participation. The data were analyzed using descriptive statistics, validity and reliability testing, and simple linear regression with SPSS version 26. The results show that all research instruments met the validity and reliability requirements, with Cronbach’s Alpha values exceeding 0.60. The regression analysis indicates that psychological factors have a positive and significant effect on social factors, as shown by a t-value of 21.232, a significance value of 0.000, and a coefficient of determination of 0.818. These findings indicate that psychological factors explain 81.8 percent of the variation in students’ social factors. Therefore, strengthening self-efficacy, confidence, motivation, and psychological readiness is essential for improving social interaction and encouraging students’ active participation in academic activities.